Pelaksanaan Mediasi Tentang Sengketa Perbatasan Tanah Di Kota Jambi - Leo Mardani; Isran Idris (Universitas Jambi, Fakultas Hukum, 2021)
This article discusses the mediation of land border disputes. The increase in land cases in the courts raises the desire to speed up the settlement process through a pattern of settlement outside the court. Based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency Number 11 of 2016 concerning Settlement of Land Cases, land disputes can be resolved through mediation outside the court. Mediation model that is suitable in the resolution of land disputes is interest-based interest-based mediation, namely the focus of mediation is directed at the substance of the best interests for both parties based on aspects of joint resolution by resolving the root causes, avoiding prolonged conflict between the parties, as well as the desire to have long-term good relationship. Abstrak Artikel ini membahas tentang pelaksanaan mediasi sengketa perbatasan tanah. Meningkatnya perkara tanah di pengadilan memunculkan keinginan untuk mempercepat proses penyelesaian melalui pola penyelesaian di luar pengadilan. Berdasarkan Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 11 Tahun 2016 tentang Penyelesaian Kasus Pertanahan, sengketa tanah dapat diselesaikan melalui mediasi di luar pengadilan. Model mediasi yang cocok dalam penyelesaian sengketa tanah adalah mediasi berbasis kepentingan interest based, yaitu fokus mediasi diarahkan pada substansi kepentingan terbaik bagi kedua belah pihak berdasarkan pada aspek penyelesaian bersama dengan cara menyelesaikan akar persoalan, menghindari konflik berkepanjangan antara para pihak, serta adanya keinginan untuk mempunyai hubungan baik jangka panjang.